Protein deficiency reduces efficacy of oral attenuated human rotavirus vaccine in a human infant fecal microbiota transplanted gnotobiotic pig model. Issue 42 (8th October 2018) - Miyazaki, Ayako; Kandasamy, Sukumar; Michael, Husheem; Langel, Stephanie N.; Paim, Francine C.; Chepngeno, Juliet; Alhamo, Moyasar A.; Fischer, David D.; Huang, Huang-Chi; Srivastava, Vishal; Kathayat, Dipak; Deblais, Loic; et al.
Highlights: Protein deficiency impacted immunity and reduced human RV vaccine efficacy. Human infant fecal microbiota exacerbated the negative effects of protein deficiency. Immunological dysfunction could have been induced by altered tryptophan catabolism. Our findings provide an explanation for RV vaccine failures in malnourished children. Abstract: Background: Low efficacy of rotavirus (RV) vaccines in developing African and Asian countries, where malnutrition is prevalent, remains a major concern and a challenge for global health. Methods: To understand the effects of protein malnutrition on RV vaccine efficacy, we elucidated the innate, T cell and cytokine immune responses to attenuated human RV (AttHRV) vaccine and virulent human RV (VirHRV) challenge in germ-free (GF) pigs or human infant fecal microbiota (HIFM) transplanted gnotobiotic (Gn) pigs fed protein-deficient or -sufficient bovine milk diets. We also analyzed serum levels of tryptophan (TRP), a predictor of malnutrition, and kynurenine (KYN). Results: Protein-deficient pigs vaccinated with oral AttHRV vaccine had lower protection rates against diarrhea post-VirHRV challenge and significantly increased fecal virus shedding titers (HIFM transplanted but not GF pigs) compared with their protein-sufficient counterparts. Reduced vaccine efficacy in protein-deficient pigs coincided with altered serum IFN-α, TNF-α, IL-12 and IFN-γ responses to oral AttHRV vaccine and the suppression of multiple innate immune parameters and HRV-specific IFN-γ producing T cells post-challenge. In protein-deficient HIFM transplanted pigs, decreased serum KYN, but not TRP levels were observed throughout the experiment, suggesting an association between the altered TRP metabolism and immune responses. Conclusion: Collectively, our findings confirm the negative effects of protein deficiency, which were exacerbated in the HIFM transplanted pigs, on innate, T cell and cytokine immune responses to HRV and on vaccine efficacy, as well as on TRP-KYN metabolism.